Rekonstruksi Pemikiran Pendidikan Islam: Integrasi Ilmu Agama dan Sains sebagai Paradigma Keilmuan - Asdianur Hadi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The fragmentation between religious knowledge and science remains one of the major challenges in contemporary Islamic education. This condition has weakened the holistic character of education and contributed to the emergence of learners who are intellectually capable but often detached from spiritual and ethical foundations. This article aims to analyze the reconstruction of Islamic educational thought through the integration of religious knowledge and science as a paradigm of knowledge. The study employs a qualitative approach using library research by examining various contemporary scholarly works on dichotomy of knowledge, Islamization of knowledge, integration-interconnection, and integrative Islamic education. The findings show that the integration of religious knowledge and science is not merely a curricular combination, but an epistemological effort to restore the unity of knowledge in Islam. This integration places revelation, reason, and empirical inquiry in a mutually reinforcing relationship. In addition, the integrative paradigm is relevant for strengthening curriculum development, learning processes, character formation, and the institutional transformation of Islamic education in the contemporary era. Thus, the reconstruction of Islamic educational thought requires an integrative, holistic, and contextual framework so that Islamic education can produce generations who are spiritually grounded, intellectually competent, and socially responsible.